Aryl hydrocarbon receptor role in chronic inflammatory skin diseases: a narrative review - Dec, Michał; Arasiewicz, Hubert (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2024)
The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that has gained increasing attention in the field of dermatology due to its multifaceted role in skin health and disease. This review provides a comprehensive overview of the current state of knowledge regarding the AHR and its implications in dermatological conditions. The AHR is well known for its involvement in xenobiotic metabolism, particularly in response to polycyclic aromatic hydrocarbons and dioxins. However, recent research has unveiled its pivotal role in the skin immune response, barrier function, and homeostasis. The AHR signalling pathway is intricately linked to various dermatological disorders, including psoriasis, atopic dermatitis, acne and hidradenitis suppurativa. In this review, we delve into the molecular mechanisms through which AHR activation influences skin physiology and highlight how dysregulation can lead to pathological conditions. Moreover, we discuss the emerging therapeutic potential of AHR modulators in the treatment of skin diseases. In conclusion, the AHR is a pivotal player in dermatology, with a multifaceted role in skin physiology and pathology. Understanding the intricacies of AHR signalling in the skin offers promising avenues for the development of novel therapies and preventive strategies for various dermatological conditions. Further research is warranted to elucidate the full scope of AHR’s contributions to dermatology and its potential as a therapeutic target.